HECK’S DISEASE IN ELDERLY MALE - Sen, Suman; Sheuli Sen (Journal of Ayub Medical College Abbottabad, 2021)
Heck’s disease is also known as focal epithelial hyperplasia (FEH). It was named by Dr Archard Heck et al in the year 1965. It is a rare form of viral infection occurring in oral mucosa. It mostly affects children’s who belongs to the Eskimos, Navajo and other Native American tribes but rarely seen in Asians.1,2 The prime etiological factor is human papilloma virus (HPV) type 13 or 32. It is mostly seen in adolescent age group. Among these 2 types the subtype 32 of HPV tends to cause the disease more in the older individuals. Intraorally both keratinized and non-keratinized surfaces have been involved by HPV. It has equal occurrence rate in both males and females.2 The clinical manifestation of these lesion is numerous small whitish or normal in colour papules or nodules mostly in lower labial mucosa followed by buccal mucosa and tongue and less commonly noted on the upper labial mucosa, gingiva and palate region.3